Community Empowerment Through the Utilization of Zakat for Productive Ventures in Sleman Regency - Harahab, Yulkarnain (Faculty of Law Universitas Padjadjaran, 2024)
This research aims to determine and analyze the empowerment of the community through the utilization of zakat for productive ventures in Sleman Regency and the inhibiting factors in the community empowerment through the utilization of zakat for productive ventures. Data collection was conducted through document studies and interviews with respondents. The collected data were then analyzed qualitatively using a normative juridical approach. Based on the research conducted, the following conclusions were drawn: first, community empowerment through the utilization of zakat for productive ventures in Sleman Regency is focused on the economic sector through the provision of revolving capital and the provision of livestock assistance to groups or individuals classified as poor and still capable of working or doing business. The provision of zakat funds is carried out through grants or qardhul hasan contracts. Community empowerment through the utilization of zakat for productive ventures is in line with the provisions of Article 27 of Law Number 23 of 2011 concerning Zakat Management and Articles 32, 33, and 34 of Minister of Religious Affairs Regulation Number 52 of 2014. Second, inhibiting factors in community empowerment through the utilization of zakat for productive ventures include limited zakat funds to be distributed, limited assistance personnel, and declining motivation among some recipients of productive zakat assistance. To overcome these obstacles, cooperation with third parties is needed in providing funds and assistance personnel, as well as in motivating zakat recipients.